Investigating Methylene Blue Removal from Aqueous Solution by Cysteine-Functionalized Mesoporous Silica. (15th June 2021) - Beagan, Abeer M.
Abstract : In this study, mesoporous silica nanoparticles (MSNs) were synthesised using the Stober method and functionalised with cysteine (MSN-Cys) for removal of Methylene Blue (MB) from aqueous solution using the batch method. The adsorbent nanoparticles were characterised by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), FTIR, BET, and TGA. Several influential factors on the adsorption of MB onto the surface of MSN-Cys particles were investigated, including pH, initial concentration, and contact time. The adsorption capacity of MB from aqueous solution increased from circa 70 mg/g MSN-Cys in acidic media to circa 140 mg/g MSN-Cys in basic media. Adsorption isotherms and kinetic models of adsorption were used to clarify the adsorption process. The measured adsorption isotherm was fitted with a Freundlich model for all solutions, and the kinetic model was determined to be pseudo-second-order.